The unnameable: limits of language in early analytic philosophy - Price, M (2015)
This thesis concerns the view, shared by Frege, Russell and the early Wittgenstein, that there are entities that cannot be named. Chapter 1 clarifies the particular form this commitment takes in the work of these three authors. The chapter also details a distinctive cluster of philosophical difficulties attending the view certain entities are unnameable, and explores the relation between unnameability and inexpressibility. The remaining chapters are devoted to investigating what grounds there are for countenancing the unnameable. The particular focus throughout is Frege's thesis that concepts cannot be named. Chapters 2 and 3 are devoted to giving a detailed hearing to two arguments for Frege's thesis distinguishable in the locus classicus, 'On Concept and Object'. The first argument concerns the relationship between co-reference and intersubstitutability; the second concerns the unity of thought. It is contended that these arguments fail to substantiate Frege's thesis. Chapters 4 and 5 examine two further arguments for Frege's rejection of singular reference to concepts. The first is based upon the alleged impossibility of expressing identities between objects and concepts; the second draws on upon considerations pertaining to diagonalization and Russell's paradox. It is contended that each of these arguments can be resisted in defence of singular reference to concepts.